Reviews Summer 2020. Issue 1 (1st September 2020) - Marinazzo, Adriano; Vervoort, Stefaan; Allen, Matthew; Astengo, Gregorio; Smyth-Pinney, Julia
Marinazzo, A. A Review of William E. Wallace, Michelangelo, God's Architect: The Story of His Final Years and Greatest Masterpiece . Princeton and Oxford: Princeton University Press, 2019. Vervoort, S. A Review of Matthew Mindrup, The Architectural Model: Histories of the Miniature and the Prototype, the Exemplar and the Muse . Cambridge, MA, and London: The MIT Press, 2019. Allen, M. A Review of Joseph Bedford, ed., Is There an Object-Oriented Architecture? Engaging Graham Harman . London and New York: Bloomsbury Academic, 2020. Astengo, G. A Review of Vaughan Hart, Christopher Wren: In Search of Eastern Antiquity . London: Yale University Press, 2020. Smyth-Pinney, J. A Review of Maria Beltramini and Cristina Conti, eds., Antonio da Sangallo il Giovane: Architettura e decorazione da Leone X a Paolo III . Milan: Officina libraria, 2018.